Tobacco Cessation Counseling - Joseph D'Ambrosio; Julie Wagner; Miranda Jennings; Carol Pfeiffer (Association of American Medical Colleges, 2013)
Abstract Tobacco use is a major preventable cause of premature death. It is also a risk factor for a variety of oral and systemic diseases such as cardiovascular and lung diseases, as well as several types of cancer including mouth and oropharyngeal neoplasms. The majority of individuals who smoke would like to quit, and they are more likely to be successful when motivated and assisted by a health care provider. Clinicians are in the unique position to promote both general and oral health and to help their patients change high-risk behaviors such as smoking, but they do not consistently take advantage of this opportunity. This is in in part because many health care providers feel that they lack the knowledge and expertise to address tobacco intervention with their patients. This resource contains a PowerPoint presentation, instructions, and a 20-minute video on how to administer the five major components of a brief tobacco intervention (i.e., Ask, Advise, Assess, Assist, and Arrange) as specified by the U.S. Department of Health and Human Services - Public Health Services. Health care providers may review these materials as independent learning, or use them to direct small-group discussions.